Pengaruh Model Pembelajaran Kooperatif Tipe Make A Match Dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Fiqih BAB Shalat Jum’at - Mochamad Arsad Ibrahim; M. Ridwan Effendi; Enan Kusnandar (CV Putra Publisher, 2024)
This research aims to determine the influence of the Make a Match type cooperative learning model in improving student learning outcomes in the fiqh subject of the Friday prayer chapter in class 7. This is important to research considering how far the influence of the Make a Match type cooperative learning model is in improving learning outcomes. student. In this research, the Pearson product moment correlation method was used with a population of 145 people and a sample of 62 students in class 7. The theoretical analysis used for the variables of the Make a Match type cooperative learning model (Vioreza et al., 2020) and learning outcomes theory. Based on the research results, it shows that first, the Make a Match type cooperative learning model is rated as good with a mean value of 80.21. Both learning outcomes were assessed as good with a score of 16.42. Third, there is no influence of the Make a Match type cooperative learning model on student learning outcomes in the fiqh subject on Friday prayers in class 7. Because the calculated t value is 1.659 with a significance value of 0.102>0.005. So Ho is accepted and Ha is rejected, which means there is no relationship between the make a match type cooperative learning model and student learning outcomes.